Efektivitas Pelayanan Pendaftaran Calon Jemaah Haji Tahun 2023 Di Kantor Kementerian Agama Kota Bengkulu - Luki, Luki; Lorita, Evi; Maryaningsih, Maryaningsih (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
This study aims to evaluate the effectiveness of the Hajj registration service in 2023 at the Ministry of Religious Affairs Office in Bengkulu City. The research used a descriptive qualitative method with data collected through observation, interviews, and documentation. Four informants participated, including two ministry staff and two prospective pilgrims. Data analysis referred to Sondang P. Siagian’s eight indicators of effectiveness: clarity of goals, strategy, policy formulation, planning, appropriate programming, infrastructure availability, efficient execution, and educational supervision. Results show that the service was generally effective, though limited human resources and suboptimal technology use remain challenges. Available facilities such as waiting rooms, bank counters, and digital tools like Haji Pintar and Siskohat significantly supported the registration process. The study recommends improving staff capacity and enhancing digital system utilization to achieve more efficient service delivery.